Freshwater fish in the Waikato region : an evaluation of novel standardised data and drivers of fish distribution and abundance : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Science in Ecology at Massey University Manawatū, New Zealand - Boyce, Paul (Massey University, 2016)
Native freshwater fish populations in New Zealand are in rapid decline and continue to be affected by multiple impacts. As fish populations contract and species become rarer, monitoring and prediction of species presence and abundance throughout New Zealand becomes an increasingly important management tool. Until recently, the majority of modelling analyses in New Zealand have used small or inconsistent datasets which limit analyses to presence/absence type assessments and can make even those analyses inaccurate. Using a novel dataset that was collected using a consistent set of sampling protocols collected by Waikato Regional Council (WRC) staff in the Waikato region, New Zealand, fish presence/absence and abundance data were analysed. Models were built to predict species distributions and abundance across the region and to identify key environmental drivers determining distribution and abundance. Model performance was also assessed in comparison to a commonly used freshwater fish dataset – the New Zealand Freshwater Fish Database (NZFFDB). Drivers of the distribution and abundance of all sampled species were identified and three species were investigated in further detail: longfin eels (Anguilla dieffenbachii); shortfin eels (Anguilla australis); and redfin bullies (Gobiomorphus huttoni). Abundance and distribution predictions were mapped throughout the Waikato region River Environment Classification (REC) waterways for these three species. An analysis of population demographics for redfin bully mean length comparing the east and west coasts of the Waikato region was also undertaken. Sampling consistency (mean button time and mean area fished) within the WRC dataset was high and model performance was higher for the majority of species using the WRC dataset compared with NZFFDB data. Comparisons between reference and impact sites for the three species revealed significantly higher relative abundance of redfin bullies at reference sites, along with significantly larger longfin eels (subject to methodological bias). Shortfin eel relative abundance was significantly higher at impact sites. A greater proportion of very small and small shortfin eels were caught during sampling with longfin eels having relatively greater numbers in larger size classes. Substantial differences in the size of eels caught using different methodologies were also found with larger individuals caught using netting methods compared with electric fishing. Significant differences in mean length between years for redfin bullies were identified and a significant difference in mean length between east and west coast populations was found. This difference was also present within the NZFFDB dataset. Distribution and population characteristics for the three species were examined in reference to land use and model identified drivers of variation. Distance, elevation, temperature, and slope frequently ranked high as drivers of native fish distribution and abundance. Longfin eels and redfin bullies appear to be excluded from areas of intensive agriculture throughout the central Waikato with redfin bullies in particular predominantly limited to areas of remaining indigenous forest cover. This pattern is mirrored by shortfin eels which have high predicted presence and relative abundance values in lowland agricultural areas. Models of native richness and abundance IBI scores also show this pattern of distribution across the Waikato region. Both native richness and abundance IBI scores are higher at the coast where intensive agriculture is absent and a greater proportion of reference sites are available. Scores consistently decrease moving inland towards lowland catchments at a rate that is likely higher than innate species distributions due to diadromy alone. Predictive modelling for both abundance and presence data provided extensive mapping opportunities for waterways throughout the Waikato region in the River Environment Classification network. This tool used in conjunction with a robust dataset provided a versatile and accurate method for describing fish populations in the region. Many characteristics of the biology and life history of native species were able to be explored within this study, raising questions about recruitment and population biology of fish species, in particular redfin bullies. The importance of establishing consistent sampling protocols throughout New Zealand freshwater monitoring programmes is exemplified in the ability to uncover these characteristics accurately.